What do Parents and Children talk about at a Natural History Museum?. (October 2016) - To, Cheryl; Tenenbaum, Harriet R.; Wormald, Daniel
Abstract: This study investigated the ways in which families constructed an understanding of evolution exhibits at a natural history museum. We examined museum visitors' use of exhibit text and the types of evolution‐related talk in parent‐child conversations while visiting the chimp/human and the artiodactyl exhibits. Participants were 52 families with children aged 2‐ to 11‐years who agreed to be digitally recorded. Analyses of parent‐child conversations indicated that families who read exhibit text were more likely to stay longer at the exhibits and to encounter the intended content of the exhibits than families who did not read the text. On‐topic conversations tended to focus on labelling and describing the exhibit content rather than talking about evolutionary concepts. Physical descriptions of exhibit displays allowed children to make inferences about novel entities (i.e., those in the exhibits) based on prior knowledge.